Neonatal pain and reduced maternal care: Early-life stressors interacting to impact brain and behavioral development. (7th February 2017) - Mooney-Leber, Sean M.; Brummelte, Susanne
Highlights: Neonatal pain & reduced maternal care are both associated with adverse outcomes in preterm infants. These adverse outcomes may be due to the stress-induced activation of the HPA axis. Kangaroo care or skin-to-skin contact may negate some of the negative outcomes by dampening the HPA axis response. More research is needed to better understand mechanisms underlying Kangaroo care's positive impact. Abstract: Advances in neonatal intensive care units (NICUs) have drastically increased the survival chances of preterm infants. However, preterm infants are still exposed to a wide range of stressors during their stay in the NICU, which include painful procedures and reduced maternal contact. The activation of the hypothalamic–pituitary–adrenal (HPA) axis, in response to these stressors during this critical period of brain development, has been associated with many acute and long-term adverse biobehavioral outcomes. Recent research has shown that Kangaroo care, a non-pharmacological analgesic based on increased skin-to-skin contact between the neonate and the mother, negates the adverse outcomes associated with neonatal pain and reduced maternal care, however the biological mechanism remains widely unknown. This review summarizes findings from both human and rodent literature investigating neonatal pain and reduced maternal care independently, primarily focusing on the role of the HPA axis and biobehavioral outcomes. The physiological and positive outcomes of Kangaroo care will also be discussed in terms of how dampening of the HPA axis response to neonatal pain and increased maternal care may account for positive outcomes associated with Kangaroo care.